1997
DOI: 10.1523/jneurosci.17-05-01795.1997
|View full text |Cite
|
Sign up to set email alerts
|

Differential Binding Profile and Internalization Process of Neurotensin via Neuronal and Glial Receptors

Abstract: Two G-protein-coupled receptors for the tridecapeptide neurotensin (NT) have been identified and cloned in mammalian brain: a high-affinity (K d ϭ 0.3 nM) receptor, sensitive to the antagonist SR 48692 but insensitive to levocabastine, and a lower-affinity (K d ϭ 2-4 nM) receptor, sensitive to levocabastine but with poor affinity for SR 48692. Although there is good evidence that the high-affinity site is predominantly expressed in neurons, little is known of the cellular localization of the low-affinity recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 51 publications
(57 reference statements)
3
32
0
Order By: Relevance
“…However, the increase in spontaneous EPSC frequency caused by NT(8^13) is blocked by SR142948A, a compound with high a⁄nity for both type 1 (NTR1) and type 2 NT (NTR2) receptors Trudeau, L.-E., unpublished results). It has been proposed that dopaminergic neurones preferentially express NTR1 and not NTR2, which may be preferentially expressed in astrocytes (Nouel et al, 1997). It is thus likely that most e¡ects observed here were mediated by NTR1.…”
Section: Implication Of Nt Receptorsmentioning
confidence: 74%
“…However, the increase in spontaneous EPSC frequency caused by NT(8^13) is blocked by SR142948A, a compound with high a⁄nity for both type 1 (NTR1) and type 2 NT (NTR2) receptors Trudeau, L.-E., unpublished results). It has been proposed that dopaminergic neurones preferentially express NTR1 and not NTR2, which may be preferentially expressed in astrocytes (Nouel et al, 1997). It is thus likely that most e¡ects observed here were mediated by NTR1.…”
Section: Implication Of Nt Receptorsmentioning
confidence: 74%
“…Binding of fluo-NT was also assessed in cells naturally expressing the high-affinity neurotensin receptor (NT-1; SN17 neuron-neuroblastoma hybrid cells (26); primary neurons in culture (27)) or the low-affinity NT receptor (NT-2; astrocytes in culture (27)). Binding was carried out at 4 o C or at 37 o C in the presence of the endocytosis inhibitor, phenylarsine oxide (PAO), to prevent ligand sequestration and/or internalization.…”
Section: Binding To Cultured Cellsmentioning
confidence: 99%
“…Neurotensin has two receptors in the adult brain (Kitabgi et al, 1987), one which has a low anity for NT, termed neurotensin receptor-2 NTR-2 (Chalon et al, 1996), which has been shown to be involved in the formation of ligand-induced glial cell-surface receptor clusters that do not undergo subsequent internalization, the function of which has yet to be determined (Nouel et al, 1997). The second receptor has a high anity for NT and is called neurotensin receptor-1 (NTR-1; Tanaka et al, 1990) and is located presynaptically in the striatum and postsynaptically in the nucleus accumbens (Schotte et al, 1988).…”
Section: Introductionmentioning
confidence: 99%